대학생의 공감능력이 행복감에 미치는 영향 - 감사성향과 도움행동의 매개효과 - 김은주; 정은정; Kim, Eun-Ju; Chung, Eun-Jung (한국콘텐츠학회 논문지, 18(2), 2018)
The purpose of this study is to investigate the relationship among empathy ability, gratitude tendency, helping behavior, and happiness of college students and whether gratitude tendency and help behaviors are mediators in the relationship between empathy ability and happiness. For this purpose, Date were collected from 559 college students in S and K city. The SPSS 20.0 program was used to analyze the statistical data such as the mean and standard deviation of the data. To analyze the validity of the study, it conducted confirmatory factor analysis using AMOS. Finally, we analyzed the effect of empathy on happiness by using the bootstrap procedure in order to investigate the mediating effects of gratitude tendency and helping behavior. The results of the study are as follows. First, the correlation of each was positive. Second, in the relationship between empathy ability and happiness, the gratitude tendency was a statistically significant mediator. Third, helping behavior was a statistically significant mediator between empathy and happiness. Fourth, in the relationship between empathy ability and happiness, it did not do dual mediate to the gratitude tendency and help behavior. The implications and limitations of this study are discussed. 본 연구는 대학생의 공감능력, 감사성향, 도움행동, 행복감 간의 관계를 살펴보고, 공감능력과 행복감의 관계에서 감사성향과 도움행동이 매개변인의 역할을 하는지에 대한 탐색을 실시하였다. 이를 위해 S지역과 K지역에 재학 중인 남녀 대학생 559명을 대상으로 자료를 수집하였다. SPSS 20.0 프로그램을 사용하여 자료의 평균, 표준편차의 등의 전반적인 기술통계분석을 실시하였고, 이후 연구변인의 타당성을 분석하기 위해 AMOS를 사용하여 확인적 요인분석을 실시하였다. 마지막으로 공감능력이 행복감에 미치는 영향에서 감사성향과 도움행동이 매개효과를 알아보기 위해 부스트랩(bootstrap) 절차에 따라 분석을 실시하였다. 연구결과는 다음과 같다. 첫째, 공감능력, 감사성향, 도움행동과 행복감 간의 상관관계를 분석한 결과, 공감능력은 행복감, 감사성향, 도움행동에 정적 상관관계를 나타냈다. 둘째, 공감능력과 행복감의 관계에서 감사성향은 통계적으로 유의한 매개 변인이었다. 셋째, 공감능력과 행복감의 관계에서 도움행동은 통계적으로 유의한 매개 변인이었다. 넷째, 공감능력과 행복감의 관계에서 감사성향과, 도움행동은 이중 매개하지 않았다. 이를 토대로 본 연구의 시사점과 제한점에 관하여 논의하였다.